A sign and a wonde r the redactional formation of Isaiah 18-20 - Cook, Paul M. 1976- (Vetus Testamentum, Supplements, 2011)
While many studies on Isaiah are interested in the formation of the book, relatively few have addressed the development of the oracles concerning foreign nations. Like many other prophetic books, the book of Isaiah contains a section of foreign nations oracles (Isaiah 13-23), but within this collection is a smaller grouping of literary material that deals with the nations of Cush (Ethiopia) and Egypt (Isaiah 18-20). This book considers the formation of this smaller group about Cush and Egypt within the literary context of the growth of the larger collection and the development of these individual chapters. This book also contributes a fresh approach to the formation of foreign nations oracles in Isa 13-23.